2016
DOI: 10.1007/s40264-016-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitor-Induced Interstitial Lung Disease: Clinical Features, Diagnostic Challenges, and Therapeutic Dilemmas

Abstract: Since the approval of the first molecularly targeted tyrosine kinase inhibitor (TKI), imatinib, in 2001, TKIs have heralded a new era in the treatment of many cancers. Among their innumerable adverse effects, interstitial lung disease (ILD) is one of the most serious, presenting most frequently with dyspnea, cough, fever, and hypoxemia, and often treated with steroids. Of the 28 currently approved TKIs, 16 (57 %) are reported to induce ILD with varying frequency and/or severity. The interval from drug administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 127 publications
1
60
0
1
Order By: Relevance
“…33,34 They are also limited due to radiation-induced lung injury and TKI-induced interstitial lung disease. 35,36 In our study, we demonstrated that irradiation-induced NF-κB activation plays a vital role in resistance to radiotherapy and EGFR-TKIs in NSCLC. NF-κB, as a stress-inducible transcription factor, is known to induce the transcription of antiapoptotic genes such as B-cell lymphoma-extra large (Bcl-XL) and X-linked inhibitor of apoptosis protein (XIAP).…”
Section: Discussionmentioning
confidence: 63%
“…33,34 They are also limited due to radiation-induced lung injury and TKI-induced interstitial lung disease. 35,36 In our study, we demonstrated that irradiation-induced NF-κB activation plays a vital role in resistance to radiotherapy and EGFR-TKIs in NSCLC. NF-κB, as a stress-inducible transcription factor, is known to induce the transcription of antiapoptotic genes such as B-cell lymphoma-extra large (Bcl-XL) and X-linked inhibitor of apoptosis protein (XIAP).…”
Section: Discussionmentioning
confidence: 63%
“…However, drug induced ILD case reports and case series were published in the post marketing period for imatinib, dasatinib, nilotinib and other non BCR-ABL1 TKIs [20].…”
Section: Discussionmentioning
confidence: 99%
“…ILD has been induced not only by EGFR and BCR-ABL1 TKIs, but also TKIs that target anaplastic lymphoma kinase, platelet-derived growth factor receptor, vascular endothelial growth factor receptor, hepatocyte growth factor receptor and fibroblast growth factor receptor among other TKIs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Certaines ethnies sont plus exposées à une toxicité pulmonaire : le risque de pneumopathie au gefitinib est de 2 % au Japon contre 0,3 % aux États-Unis [2,21]. L'état pulmonaire préexistant (pneumopathie interstitielle diffuse, pneumonectomie, cancer pulmonaire) est susceptible de favoriser l'apparition d'une PM, comme cela est décrit pour le méthotre-xate chez les patients atteints d'une polyarthrite rhumatoïde, l'amiodarone, les inhibiteurs des tyrosines kinases et les inhibiteurs des points de contrôle immunitaire [12,22,23]. Pour ces derniers, il existe un risque accru de PM lorsqu'ils sont administrés pour un cancer pulmonaire comparé à un mélanome.…”
Section: Quels Patients ?unclassified